(untitled) (Journal of the College of Basic Education, 2022)
This study aims at investigating The Effect of Entwistle Model in Developing Metacognitive Thinking Skills in the Subject of Arabic Grammar for Preparatory Stage Students by investigating the validity of the following hypotheses: There is no statistically significant differences at level 0.05 between the average of the scores of experimental group students who studied the subject of Arabic grammar according to Entwistle Model, and the average of the scores of control group students who studied the subject of Arabic grammar according to the conventional way in accessing the skills of metacognitive thinking posttest. There is no statistically significant difference at level 0.05 between the average of the scores of experimental group students who studied the subject of Arabic grammar according to Entwistle Model in the assessment of metacognitive thinking pretest and posttest. There is no statistically significant difference at level 0.05 between the average of the scores of the control group students who studied the subject of Arabic grammar according to the conventional way in the assessment of metacognitive thinking pretest and posttest. The researcher applied the experimental method with partial control. The sample of the study consisted of 64 students divided into 32 students in the experimental group and 32 students in the control group. He balanced the groups in the variables of age in months, and the scores of the pretest of metacognitive thinking. In the experiment, the researcher taught seven grammatical topics in the subject of Arabic grammar for the fourth literary class. Select researcher behavioral goals of the topics grammatical rule of (83) goals, built a researcher measure thinking skills over knowledge in Arabic language rules for students fourth grade literary, promising researcher (14) plan by seven plans for the experimental group, and seven of the officer. He identified the behavioral aims for the topics. He also built a scale for assessing metacognitive thinking skills in the subject of Arabic grammar for the fourth literary class. The researcher discovered that the students of the experimental group who studied the subject of Arabic grammar according to Entwistle Model exceeded the control group students who studied the subject of Arabic grammar according to the conventional way. In the light of the findings, the researcher recommends the use of Entwistle Model in teaching the subject of Arabic grammar for the fourth literary class due to its effect in developing metacognitive thinking. The researcher also suggests conducting similar studies on other educational material like literature and texts, reading, and rhetoric.